Aplikasi Identifikasi Pola Pembelian Konsumen Menggunakan Algoritma Apriori pada Sukoco Batik Solo - Pipin Widyaningsih (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Sukoco Batik Solo is a batik shop that offers various types of batik. Sukoco Batik Solo must develop a marketing strategy to optimize sales. One strategy that can be used is to identify consumer purchasing tendensies patterns by utilizing product sales notes. Apriori algorithm is applied to analyze a collection of sales notes to find a combination of products purchased at one time. The application is made using the code igniter framework with the PHP programming language and MySQL database. The results showed that the application can help generate information on consumer purchasing patterns. Transaction data were analyzed using the a priori algorithm with a minimum support value of 40% and a minimum confidence value of 60%. The results obtained from the a priori algorithm process is one association rule with two combinations of product items, namely Batik Lawasan 1 and Batik Lawasan 2. The association rules for Batik Lawasan 1 and Batik Lawasan 2 have a minimum support value of 40% and a minimum confidence value of 66.67%. The results of the analysis of consumer purchasing patterns can be used by management in placing products, product inventory priority and designing price discount strategies for the combination of product items formed.